THE BURNOUT SYNDROME OF EDUCATIONAL WORKERS - Maric, Nada; Maksimović, Nataša; Bulat, Petar (Medicinski podmladak, 2020)
Since it started being mentioned in scientific literature in 1970’s till nowadays, burnout syndrome become widely explored phenomenon. It is about stressful reaction at workplace that is characterized by emotional exhaustion, depersonalization/cynicism and reduced feeling of personal achievements. However, authors agreed that it is a multicausal phenomenon and they identified a large number of situational and individual factors involved in its creation. Situational factors relate to working environment and include characteristics of work and profession itself, so as the way of work organization, while individual factors include personality characteristics, sociodemographic characteristics and various life-working attitudes of individuals. However, existence of certain contradictions was noticed and its variation from one country to another. The importance of this phenomenon is reflected due to numerous negative effects it leaves on the health of individuals, but also due to significant economic overloading of employer and the country as well. This is the reason of many researches about this syndrome and a high prevalence was observed in a wide range of professions, including teachers. Authors emphasize that importance of the research of this phenomenon among teachers is of global interest because beside already descripted negative effects on teachers, it also directly effects on educational process, but also has negative influence on mental and emotional growth of children. It is an inevitable that additional researches of this phenomenon are necessary, especially in teachers’ population, in order to better understand this phenomenon. This knowledge would enable us to form targeted interventions in order to reduce exposure to stress at work and reduce the prevalence of this syndrome among teachers.
Keywords: occupational stress; burnout syndrome; educational personnel; teachers, working environment